(untitled) (Texas Journal of Engineering and Technology, 2022)
The educational environment today is rapidly changing due to new realities and new learning needs. One of the currently most demanded areas of innovation is the organization of new forms of education in a virtual educational environment. The article discusses the role of a teacher in a virtual educational environment, new functions that a modern teacher should take on, which requires new knowledge and competencies from him.